Moderating effects of Islamic work ethics on trait emotional intelligence, knowledge sharing behaviour and work performance of Muslim police investigation officers - Ruslan, Shazrin Azlin (2018)
The present study aims to investigate the role of Islamic work ethics in moderating the relationship between dimensions of trait emotional intelligence: sociability, emotionality, well-being and self-control with Knowledge Sharing Behaviour among Criminal Investigation Officers in Royal Malaysia Police. This study provides a comprehensive understanding of the ways in fostering knowledge sharing behaviour in a police force. The role of Islamic work ethics in the relationship between personality traits towards knowledge sharing behaviour has become crucial especially in an Islamic country like Malaysia. The present study has looked into the roles of individual characteristics and work ethics in knowledge sharing behaviour. The respondents of the study consisted of 351 Criminal Investigation Officers from the states of Federal Territory Kuala Lumpur and Selangor. A survey was carried out, for which a questionnaire was administered to the respondents. Analysis of the quantitative data of the study involved both the Statistical Package for Social Sciences (SPSS) version 22 and Smart-PLS version 3.0. Prior to reporting the results, it was ensured that all the necessary requirements for the measurement model analysis including both the reflective (i.e., composite reliability, convergent validity and discriminant validity) and formative measurements (i.e., VIF and outer weight significance), were satisfied. The indicators loading, composite reliability (CR) (0.911, 0.899, 0.878, 0.889) and average variance extracted (AVE) (0.506, 0.527, 0.592, 0.502) of the reflective constructs are satisfied for all construct. Upon scrutinizing the results, it was discovered that the collinearity assessment in structural model confirmed that no problems were detected in relation to the lateral collinearity (VIF<5). In addition, it was also found that three out of the five hypotheses on direct relationships between the independent variables and dependant variable are significant (p<0.05). Specifically, it was revealed through the analysis that the police officers’ higher level of sociability, and emotionality have a significant positive relationship with knowledge sharing behaviour. Besides, the results of bootstrapping appeared to suggest that three out of the four moderating effects of Islamic work ethics were supported. In other words, Islamic work ethics was found to moderate the relationships between sociability, self-control and wellbeing towards knowledge sharing behaviour.